Faktor Determinan Nasabah dalam Pemilihan Bank Syariah - Mursid, Ali; Suhartono, Entot (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2014)
The objective of the study was to investigate several factorswhich influenced the customersto select sharia/ Islamic bank, they weretechnology, religious motivation, and service quality. The data were collected by questionare as the instrument.The questionnaires were distributed to 100 respondents as the active customers of sharia bank in Semarang. The data were analysed by validity and reliability test to evaluate the questionare and by linier regretion to evaluate the influential factors of those variables. The result showedthat technology, religious motivation, and service quality significantly influencedthe customers